Longmire : The Dark Horse - Book 5 - Johnson, Craig; 1961- (New York, 2010)
Wade Barsad, a man with a dubious past and a gift for making enemies, burned his wife Marys horses in their barn; in retribution, she shot him in the head six times, or so the story goes. But Sheriff Walt Longmire doesnt believe Marys confession and is determined to dig deeper. Unpinning his star to pose as an insurance investigator, Walt visits the Barsad ranch and discovers that everyone in town--including a beautiful Guatemalan bartender and a rancher with a taste for liquor--had a reason for wanting Wade dead. -- Book cover.
Keywords: Longmire, Walt (Fictitious character); Fiction; Sheriffs; Wyoming; Fiction; Wyoming; Fiction; Western fiction